Paid Work characteristics of Mothers with infants - Baxter, Jennifer; Gray, Matthew (My University, 2006)
The labour market participation of mothers with young children has undergone significant change in recent decades. Despite the extent of these changes, little is known about the types of jobs in which mothers with infants are employed. This paper, drawing on data from the first wave of the research study, Growing Up in Australia: the Longitudinal Study of Australian Children, provides a detailed analysis of the jobs in which mothers are employed at this critical time in the family life course.
Family Matters
Keywords: Employment; Families; Families -- Mothers; Families and relationships; Labour market; Employment; Families; Mothers; Employment and unemployment; Families and relationships